Inhibition of innate immune response ameliorates Zika virus-induced neurogenesis deficit in human neural stem cells. - Pei Xu; Junling Gao; Chao Shan; Tiffany J Dunn; Xuping Xie; Hongjie Xia; Jing Zou; Beatriz H Thames; Amulya Sajja; Yongjia Yu; Alexander N Freiberg; Nikos Vasilakis; et al. (Public Library of Science (PLoS), 2021)
Global Zika virus (ZIKV) outbreaks and their strong link to microcephaly have raised major public health concerns. ZIKV has been reported to affect the innate immune responses in neural stem/progenitor cells (NS/PCs). However, it is unclear how these immune factors affect neurogenesis. In this study, we used Asian-American lineage ZIKV strain PRVABC59 to infect primary human NS/PCs originally derived from fetal brains. We found that ZIKV overactivated key molecules in the innate immune pathways to impair neurogenesis in a cell stage-dependent manner. Inhibiting the overactivated innate immune responses ameliorated ZIKV-induced neurogenesis reduction. This study thus suggests that orchestrating the host innate immune responses in NS/PCs after ZIKV infection could be promising therapeutic approach to attenuate ZIKV-associated neuropathology.